PENGARUH KONSENTRASI DAN SUHU LARUTAN GULA PADA PROSES DEHIDRASI OSMOTIK BUAH NAGA (Hylocereus sp.): Effect of Concentration and Temperature of Sugar Solution in The Process of Osmotic Dehydration of Dragon Fruit (Hylocereus sp.) - Spetriani Spetriani (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2019)
ABSTRACTOsmotic dehydration is a water removing process that carried out on a object by immersing the object into an hyper-tonic (osmotic) solution. The process is commonly applied on pre-drying of fruit. The purpose of this research is to investigate the effect of concentration and temperature of osmotic solution on moisture content change, total dissolved solids change and to determine of water diffusion coefficient and solid diffusion coefficient during the process of osmotic dehydration of dragon fruit. Factorial design was used with 2 factors, each consisting of 3 levels with 3 replication. The treatment on this research are : solution consentration of 30 °Brix, 50 °Brix, and 70 °Brix and solution temperature of 30 °C, 40 °C, and 50 °C were applied to this research. The osmotic dehydration process lasts for 8 hours. Initial moisture content of dragon fruit used for the research between 511.17-665.97 (% db). Moisture and solid diffusivities were in the range of 2.810 x 10-8 m²/s - 7.003 x 10-8 m²/s and 0.973 x 10-8 m²/s until 4.734 x 10-8 m²/s. The activation energy for diffusion of water to the concentration of 30 °Brix, 50 °Brix, and 70 °Brix respectively is 9.963 kJ/mol, 3.249 kJ/mol, and 5.372 kJ/mol. While the activation energy for diffusion of solids is 24.946 kJ/mol, 8.908 kJ/mol, and 27.343 kJ/mol. Keywords: dragon fruit, moisture diffusivity, osmotic dehydration, solid diffusivity ABSTRAK Dehidrasi osmotik adalah suatu proses pengeluaran air yang dilakukan terhadap suatu bahan dengan cara merendam bahan tersebut ke dalam suatu larutan hipertonik. Proses ini pada umumnya diaplikasikan untuk pra-pengeringan buah-buahan. Tujuan penelitian ini adalah untuk mengkaji pengaruh perlakuan konsentrasi dan suhu terhadap perubahan kadar air, perubahan total padatan terlarut dan untuk menentukan nilai koefisien difusi air dan difusi padatan selama proses dehidrasi osmotik pada buah naga. Digunakan rancangan faktorial dengan 2 faktor yang masing-masing terdiri atas 3 taraf dengan 3 kali ulangan. Perlakuan yang digunakan pada penelitian ini adalah variasi konsentrasi larutan 30 °Brix, 50 °Brix, dan 70 °Brix dan suhu larutan 30 °C, 40 °C, dan 50 °C. Proses dehidrasi osmotik berlangsung selama 8 jam. Kadar air awal buah naga yang digunakan untuk penelitian berkisar antara 511,17-665,97 (%db). Nilai difusivitas air antara 2,810 x 10-8 m²/s – 7,003 x 10-8 m²/s dan difusivitas padatan antara 0,973 x 10-8 m²/s - 4,734 x 10-8 m²/s. Energi aktivasi untuk difusi air untuk konsentrasi 30 °Brix, 50 °Brix, dan 70 °Brix secara berurutan adalah 9,963 kJ/mol, 3,249 kJ/mol, dan 5,372 kJ/mol. Energi aktivasi untuk difusi padatan adalah 24,946 kJ/mol, 8,908 kJ/mol, dan 27,343 kJ/mol. Kata kunci: buah naga, dehidrasi osmotik, difusivitas air, difusivitas padatan